Biochemical Composition and Gonadosomatic Index of Three Major Carps in Hatnoor Reservoir, Maharashtra, India - S. Lohar, Shaikh Abdullah S. and Prakash (Journal of Ecobiotechnology, 2011)
Three major carps captured from Hatnoor reservoir were studied over a period of June 2008 to May 2010 to evaluate seasonal changes in muscle biochemistry and gonadosomatic index (GSI). During pre-breeding, breeding and post-breeding seasons, each fish species were captured and samples of muscle tissue were collected and processed for estimation of its protein, lipid and glycogen content. Weight of body and gonads of each fish species were noted. Protein, lipid and glycogen content in muscles of each carp species exhibited seasonal variations. The protein and lipid contents of three fish species showed successive decrease in their estimated values during the study period (p<0.05). Whereas muscle glycogen content in fish species under study shown significantly increased trend from June 2008 to May 2009 as well as from June 2009 to May 2010, which might be due to increased glycogenesis in muscles and accelerated conversion of liver glycogen into muscle glycogen. Low GSI of carp fish reported during October to January may be due to dormancy of gonads in post-breeding season. The GSI values correlated with increased amount of protein and lipids in both pre-breeding and breeding seasons of the fish under study may be due to augmented vitellogenesis in ovary and spermatogenesis in testes that require large amount of lipoproteins.